Agribussiness Mobile Based Learning: ADIC Model to Support Students HOTS and Life Skill in Vocational School - Harjono, Hary Soedarto; Prasetyanto, Budi; Murbojono, Rahmat (World Journal of Vocational Education and Training, 2019)
This study aimed to investigate the effect of the Attainment, Discussion, Implementation, and Conclusion (ADIC) model for learning Agribusiness in Vocational School by utilizing a delivery system model of Agribusiness to attain HOTS and life skill that suitable with material and student characteristic in the vocational school. This was a research and development (R & D) and continued with an experimental study. This study was conducted in class XI of a vocational school (SMK Negeri 10) in Muaro Jambi by involving one experimental class and one control class groups. In this case, the post-test on the experimental class was compared to post-test on control class. As a result, ADIC model as one of the delivery system models can improve and promote students’ HOTS and life skill in the current school effectively. Through the ADIC model, a teacher can take place students as a learner actively to control their learning activity, to attain their knowledge, to compose discussion material and discuss it, to conduct practice and experiment, and to conclude their experiment.